2021
DOI: 10.1097/jsm.0000000000000743
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric and Adolescent Figure Skating Injuries: A 15-Year Retrospective Review

Abstract: Objective: To analyze the characteristics of injuries sustained by young figure skaters who were evaluated at regional pediatric sports medicine clinics. Design: Retrospective chart review (2003-2017). Setting: Sports medicine clinics at a tertiary-level pediatric medical center. Patients: Two hundred ninety-four figure skaters (271 female and 23 male). Age rage:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…A recent retrospective study on figure-skating related injuries among 294 American figure skaters between 9 and 19 years of age found that 69% of the injuries were due to overuse and 31% were traumatic (Kowalczyk et al, 2019), similar to the results in this study. An overuse injury may negatively affect future sports participation and result in long-term health consequences (DiFiori et al, 2014) and is recognized to affect those exposed to repetitive loading combined with inadequate rest.…”
Section: Explanatory Variables Simple Models Multiple Modelsupporting
confidence: 89%
See 3 more Smart Citations
“…A recent retrospective study on figure-skating related injuries among 294 American figure skaters between 9 and 19 years of age found that 69% of the injuries were due to overuse and 31% were traumatic (Kowalczyk et al, 2019), similar to the results in this study. An overuse injury may negatively affect future sports participation and result in long-term health consequences (DiFiori et al, 2014) and is recognized to affect those exposed to repetitive loading combined with inadequate rest.…”
Section: Explanatory Variables Simple Models Multiple Modelsupporting
confidence: 89%
“…As in previous studies about figure skating (Han et al, 2018;Kowalczyk et al, 2019), the lower limbs seem to be more affected by an injury. This reflects figure skating's biomechanics, where the elements performed require work mainly in the foot/ankle, knee, and hip joints.…”
Section: Explanatory Variables Simple Models Multiple Modelsupporting
confidence: 76%
See 2 more Smart Citations
“…On the other hand, it has been theorized that skating athletes have a lower risk for sustaining acute injuries, such as anterior cruciate ligament (ACL) tears, when compared to other competitive female athletes [9]. Female soccer players, for instance, were known as a group of competitive athletes who have a relatively high incidence of ACL tears [10,11,12].…”
Section: Introductionmentioning
confidence: 99%